Quality Evaluation of the Ready-to-Eat Avocado cv. Hass - Nicole Roberta Giuggioli; Gabriele Chiaberto; Thais Mendes da Silva (International Journal of Food Science)
Consumer interest in avocado fruit has increased in the last decade in Europe. Nutritional and quality attributes affect the choice of these fruits, whose characteristics must also be maintained in the postharvest period. The preference regarding the feasibility of eating ripe fruits can assure and improve the success of the emerging marketing of avocados. The exposure of fruits to exogenous ethylene (C2H4) treatment can accelerate the process of fruit ripening. The aim of this work was at improving the existing knowledge about the quality traits of avocado cv. Hass fruits at the ready-to-eat stage. The most important qualitative traits (weight loss, dry matter content, hardness pulp, and external and internal fruit colour) were evaluated up to 96 hours, maintaining the fruit at two different temperatures, T1 (+8°C) and T2 (+17°C). A trained sensory panel was conducted at 96 hours to confirm the quality of avocado cv. Hass ripened with exogenous C2H4.